2002
DOI: 10.2178/jsl/1190150160
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of n-diagrams

Abstract: We consider only computable languages, and countable structures, with universe a subset of ω, which we think of as a set of constants. We identify sentences with their Gödel numbers. Thus, for a structure , the complete (elementary) diagram, Dc(), and the atomic diagram, D(), are subsets of ω. We classify formulas as usual. A formula is both Σ0 and Π0 if it is open. For n > 0, a formula, in prenex normal form, is Σn, or Πn, if it has n blocks of like quantifiers, beginning with ∃, or ∀. For a formula θ, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The next result, which follows from the proofs in [32], gives a general sufficient condition for realizing arbitrary possible Turing degrees for the existential and atomic diagrams of isomorphic copies of a structure.…”
Section: Definition 3 the (Turing) Degree Of The Isomorphism Type Ofmentioning
confidence: 91%
See 3 more Smart Citations
“…The next result, which follows from the proofs in [32], gives a general sufficient condition for realizing arbitrary possible Turing degrees for the existential and atomic diagrams of isomorphic copies of a structure.…”
Section: Definition 3 the (Turing) Degree Of The Isomorphism Type Ofmentioning
confidence: 91%
“…Theorem 5.7 (Harizanov, Knight and Morozov [32]). Using the notions above, assume that A is decidable, and that the relations ≤ n are c.e.…”
Section: (C 1 )mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, for an automorphically trivial structure, all isomorphic copies have the same Turing degree, and in the case of a finite language that degree must be 0 (see [13]). Harizanov, Knight and Morozov [12] showed that, while for every automorphically trivial structure M we have Richter [27] established the following general criterion for the existence of a structure whose isomorphism type has an arbitrary Turing degree. We will write A → B if A is embeddable in B.…”
Section: Turing Degrees Of Isomorphism Types Of Structuresmentioning
confidence: 99%